ПРО СТУПІНЬ ГОТОВНОСТІ СТУДЕНТІВ ДО ДОСЛІДНОЇ РОБОТИ З ПЕДАГОГІЧНОЇ ТЕМАТИКИ (Педагогіка вищої та середньої школи, 2003)
The readiness state o f higher educational establishments' students for conducting pedagogical investigations is analyzed; the reasons o f its low level and the necessity o f definite measures to provide positive dynamic development of this complex personal formation are grounded in this article.